Clinical and surgical characteristics of infected diabetic foot ulcers in a tertiary hospital of Mexico. Issue 1 (1st January 2017) - Cervantes-García, Estrella; Salazar-Schettino, Paz María
ABSTRACT: Background : The objective of this study was to determine the clinical and surgical characteristics of diabetic foot ulcers in a tertiary level hospital in Mexico. Methods : We performed a longitudinal, descriptive study from July, 2012 to August, 2015 on a sample composed of 100 patients with type 2 diabetes mellitus and infected diabetic foot ulcers. We analyzed socio-demographic variables, comorbidities, characteristics of ulcers, and the applied treatment. Results : We found that the most affected areas were the forefoot (48%) and the plantar region (55%) of the foot. Also, most of the patients arrived with advanced stages of diabetic foot ulcers, since 93% of the lesions were of grades III–V according to the Wagner classification. Moreover, lesions usually present with advanced states of infection, since 60% of the lesions were of grades 3–4 in the PEDIS scale. In addition, the great majority of the patients are prone to complications because we found that 43% of the patients suffered from hypertension, 47% of the patients had chronic kidney disease, and 45% reported smoking. In fact, 45% of the patients eventually suffered an amputation. We also found that the situation is more difficult because the great majority of the patients (96%) have a low level of education and very low income and they do not have any health insurance. Nevertheless, we also found that an efficient treatment can help in avoiding amputations, since 53% of grade IV and 25% of grade V lesions according to the Wagner system did not suffer an amputation. Conclusions : Therefore, an effective antibiotic treatment and an education of the patient on the adequate care of their lesions are essential in increasing the welfare of patients, especially when they have a low level of education.